Test of Thyristor Multicycle Surge Current and Its Simulation - XIONG Hui; LI Shiping; DUAN Ji; XU Xianwei (Kongzhi Yu Xinxi Jishu)
It is summarized the multicycle surge current test of the six-inch thyristor. The current waveforms and temperature curves in the test are given. The temperature calculation and simulation analysis is introduced in detail. Moreover, the calculation results and test results are compared, which verifies the feasibility of the simulation.